2018
DOI: 10.1155/2018/3817580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Flexural Performance and CO2 Emissions of the Voided Slab

Abstract: Reinforced concrete is regarded as one of the ideal structural materials which comprises concrete with high compressive strength and reinforcing bars with high tensile strength. However, concrete has been pointed out that it consumes a large volume of energy and emits a lot of carbon dioxide during its manufacturing. In order to lower such environmental burdens of concrete structures, a number of studies and approaches have been carried out. The voided slab is also suggested as a new method to reduce the envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The purpose of this study was to compare the CO2 emissions of two different slab systems, The additional steel materials or devices employed in the void slab systems discussed in the previous section are the main sources of carbon dioxide emissions [27]. In this regard, it is expected that VDS will produce less carbon dioxide, since both the anchoring materials and the void formers are made up of a common material other than steel.…”
Section: Lifecycle Co2 Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this study was to compare the CO2 emissions of two different slab systems, The additional steel materials or devices employed in the void slab systems discussed in the previous section are the main sources of carbon dioxide emissions [27]. In this regard, it is expected that VDS will produce less carbon dioxide, since both the anchoring materials and the void formers are made up of a common material other than steel.…”
Section: Lifecycle Co2 Assessmentmentioning
confidence: 99%
“…The previous studies employed additional steel materials or devices to anchor the void formers securely in the slabs [22][23][24][25][26]; however, as the method of installation of void formers was slightly complicated, the accuracy and speed of installation strongly depended on the skill of the construction workers. Furthermore, Cho and Na [27] indicated that the utilisation of steel materials for anchoring the void formers to the lower and upper parts of the main reinforcement would cause more environmental burdens (~28% more CO 2 emissions) compared to ordinary reinforced concrete slabs. The previous studies employed additional steel materials or devices to anchor the void formers securely in the slabs [22][23][24][25][26]; however, as the method of installation of void formers was slightly complicated, the accuracy and speed of installation strongly depended on the skill of the construction workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally, the voided slab system is an effective method for extending the span of a building or structure as it reduces the weight of concrete. Several researchers have maintained that the voided slab system would be advantageous not only in terms of structural and economic aspects but also because of its environmental friendliness [35][36][37]. From the structural design perspective, there are several studies that have examined and confirmed the stability and reliability of the voided slab system.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of the concrete as such as bending stress of fibre reinforced concrete which improves with an increase in the percentages of steel fibre. The steel fibres prevent the early deforming of the beams and increase the durability of the structure [9][10][11][12]. The NDT methods for measuring the strength of a structure are not accurate but can help in correlating the values which can help in estimating the strength of the structure and also useful for analyzing the concrete characteristics and its homogeneity.…”
Section: Introductionmentioning
confidence: 99%